Predicting the individual lactate minimum speed by T10 and T30 in swimming - de Moraes, R. C.; Barbosa, A. C.; Barroso, R.; Papoti, M.; Colantonio, E.; Andries Jr., O. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: This study investigated the relationship between the lactate minimum (LACmin) and the 10- (T10) and 30-min (T30) continuous tests in swimmers. METHODS: Twelve swimmers (78.1±3.1% of the world record) performed the LACmin (hyperlactatemia: 2×50 m all-out 8-min apart, incremental part: N.×300 m 30-s apart), T30 and T10 using the front-crawl stroke. Blood samples were collected after each stage of LACmin for lactate analysis. Swimmers were oriented to swim as fast and as constant as possible in T10 and T30. RESULTS: Speeds in T10 (1.28±0.10 m/s) and T30 (1.21±0.09 m/s) were different from LACmin (1.24±0.09 m/s). T10 and T30 speeds presented a nearly perfect relationship with LACmin and acceptable prediction errors (T10: r=0.938, P<0.001, 0.033 m/s; T30: r=0.927, P<0.001, 0.036 m/s, respectively). CONCLUSIONS: T10 and T30 can be used as indirect tests for evaluating LACmin in swimming.